(untitled) (Revista de Investigaciones Universidad del Quindío, 2013)
This paper shows the results of obtaining type egg- shell catalysts, which were obtained from: i ) the preparation of two composite materials (composites) peletized, mixing different monomers such as bisphenol A dimethacrylate glycerolate (BGMA) and triethyleneglycol (TEG), resulting the BT phase; on the other hand, were mixed urethane dimethacrylate - mixture of isomers (UDMA ) in TEG, resulting the UT phase. Both phases were mixed with alumina obtaining UTAL and BTAL supports. ii) The method of wet impregnation was used for depositing cobalt on the surface of the composites. These catalysts were characterized by ICP to evaluate the content of metal, nitrogen physisorption for studying the surface area - pore volume, optical microscopy to verify the formation of the egg- shell , XPS for identifying cobalt oxidation state, and finally through an analysis of mechanical strength. Catalytic performance was evaluated in the oxidation of benzyl alcohol, finding great differences in activity depending on the type of support used and the amount of alumina present in the catalyst surface. The selectivity towards the production of benzaldehyde was greater than 99% in all cases.